Efeito da estatina sobre a densidade óssea avaliada pela tomografia computadorizada vertebral em receptores de transplante renal - Sa, Cinara Barros De [UNIFESP] (2019)
Bone disease after successful kidney transplantation is common and represents an association of pre-existing renal osteodystrophy, the reduced renal function after renal transplantation and the consequences of transplantation specific therapies on bone. Statins are widely prescribed drugs for the treatment of dyslipidemia that have a wide range of pleiotropic effects including a possible positive effect on bone metabolism. One hundred and seventeen patients incidents in kidney transplant were randomized to receive statin or not during 12 months. Clinical evaluation, laboratorial analysis and chest-computed tomography were performed within 1 and 2 months after kidney transplantation and with 12-month follow-up. The thoracic vertebra was used to the vertebral bone density measurement. At baseline, statin group had higher BMI, total cholesterol, LDL cholesterol, triglycerides levels and malnutrition frequency than control group. At the end of follow up period, there was no significant difference in the clinical or laboratorial parameters between groups. There was no difference in vertebral bone density comparing statin and control groups neither in univariate or multivariate analysis. The main explanations for our result are the complexity of bone disease in kidney transplant recipients and the way statins were administered, probably inadequate to achieve an effective bone concentration.